Google governance: increasing the effectiveness of critical care physicians through the use of an online usergroup. Issue 1 (22nd December 2009) - Reid, C; Harper, S; Tzannes, A; Habig, K; Coombes, S; Hayes, S; Burns, B; Oh, C; Newcombe, M; Fineberg, S L; Tall, G; Novy, M
Abstract : Aims: The aim of this study was to describe the use of an online usergroup to enhance communication and productivity by critical care specialists. Methods: In this article, we provide a description of the first 6 months of use of an online usergroup by senior retrieval physicians. Results: Initially developed as a communication and online discussion tool, our online usergroup evolved to include a number of other utilities that support clinical governance. These included a repository for useful files, educational presentations, online rostering and "portfolio pages", updating aspects of an individual specialist's non-clinical activity. Its applications continue to evolve in number and utility. Participating physicians perceive an increase in organisational efficiency. Conclusions: An online usergroup such as Google Groups may provide powerful support to an organisation's clinical governance. We recommend this tool to other services with limited administrative personnel.